2013
DOI: 10.1371/journal.pone.0059368
|View full text |Cite
|
Sign up to set email alerts
|

Discrepant Fibrinolytic Response in Plasma and Whole Blood during Experimental Endotoxemia in Healthy Volunteers

Abstract: BackgroundSepsis induces early activation of coagulation and fibrinolysis followed by late fibrinolytic shutdown and progressive endothelial damage. The aim of the present study was to investigate and compare the functional hemostatic response in whole blood and plasma during experimental human endotoxemia by the platelet function analyzer, Multiplate and by standard and modified thrombelastography (TEG).MethodsProspective physiologic study of nine healthy male volunteers undergoing endotoxemia by means of a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 93 publications
1
31
0
1
Order By: Relevance
“…Studies of high-dose endotoxin infusion in healthy volunteers to model systemic inflammation have demonstrated an increase in core temperature and an acute hypercoagulability with indications of endothelial cell activation [34]. In a similar study of low-dose endotoxin infusion, we observed an induction of SIRS, hypercoagulability by TEG, and reduced platelet aggregation by Multiplate that was paralleled by increases in circulating tissue plasminogen activator [35]. Considering that hyperthermia is associated with hypercoagulability both in the present study, where no infection exists, and in the endotoxin study, it is tempting to consider hyperthermia as a contributor to the hypercoagulability that is seen in response to SIRS and sepsis [1].…”
Section: Discussionmentioning
confidence: 74%
“…Studies of high-dose endotoxin infusion in healthy volunteers to model systemic inflammation have demonstrated an increase in core temperature and an acute hypercoagulability with indications of endothelial cell activation [34]. In a similar study of low-dose endotoxin infusion, we observed an induction of SIRS, hypercoagulability by TEG, and reduced platelet aggregation by Multiplate that was paralleled by increases in circulating tissue plasminogen activator [35]. Considering that hyperthermia is associated with hypercoagulability both in the present study, where no infection exists, and in the endotoxin study, it is tempting to consider hyperthermia as a contributor to the hypercoagulability that is seen in response to SIRS and sepsis [1].…”
Section: Discussionmentioning
confidence: 74%
“…However these effects were not appreciated until 3 hours after injection with evidence of inflammation of the pancreas and systemic levels of TUCA were not analyzed. This observation may have been an adaptive response to inflammation, which has previously been shown to shutdown fibrinolysis [24]. It would not be unexpected that TUCA has tissue dependent effects on fibrinolysis.…”
Section: Discussionmentioning
confidence: 78%
“…26 Idell et al 27 in 1991 identified tissue factor as the perpetrator for excessive fibrin deposition that remained present for weeks because of decreased fibrinolysis activity. Ostrowski et al 28 recently used TEG to demonstrate fibrinolysis shutdown in healthy volunteers by administrations of endotoxin, suggesting the cross talk between inflammation and fibrinolysis. These observations are not new, as it was appreciated in the 1960s that “stress” impacts the fibrinolytic system and that there is a complex interaction with inflammation.…”
Section: Discussionmentioning
confidence: 99%